Impact response of pedestrian bridge multicellular pultruded GFRP deck panels. (1st July 2017) - Sutherland, L.S.; Sá, M.F.; Correia, J.R.; Guedes Soares, C.; Gomes, A.; Silvestre, N.
Abstract: The impact behaviour of pultruded glass fibre reinforced polymer (GFRP) multicellular footbridge deck panels was investigated via instrumented drop weight testing. Force-displacement history, maximum force, and displacement and absorbed energy at perforation were recorded. The effects of two damage protections (a resin-sand surface coating, and polyurethane foam-filled sections) and of alternative target specimen geometries (3-cells, 1-cell and single laminated flange) were investigated. Previous quasi-static test results were successfully used to estimate the impact incident energies required for perforation, thus saving material resources. The impact force-displacement behaviour was of a similar form to that of the quasi-static tests. Before damage, coated deck sections alone exhibited a strain rate effect, with the impact response stiffer than the quasi-static response. However, a similar stiffening strain rate effect was seen for all specimens after the onset of damage, which is believed to be due to rate sensitive damage propagation. The surface coating increased the perforation energy by 25%, but foam-filled sections gave no significant impact resistance improvement. Alternative geometries could be used in specific cases, but a 3-cell wide target was found to be preferable. It was shown that even relatively mild impact events such as tool drops could result in damage, or even perforation.